Strategi Pengembangan Pariwisata Berdasarkan Pengaruh Ketersediaan Infrastruktur Terhadap Keputusan Berkunjung Wisatawan - Firdaus Ikram; Despry Nur Annisa Ahmad; Yan Radhinal (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2026)
This study analyzes the influence of infrastructure availability on tourist visit decisions in Bira Village, Bulukumba. The goal is to identify the infrastructure factors that most influence tourists and determine priorities for their development. The research methods included field surveys, observations, and the distribution of online questionnaires to 100 respondents selected using the Slovin formula. Data analysis used simple linear regression to measure influence and the Analytic Hierarchy Process (AHP) to determine priorities. The results demonstrate that infrastructure availability has a positive influence on visit decisions. Further AHP analysis revealed that accessibility infrastructure and social media promotion are top priorities in the village's tourism development strategy. In conclusion, improving infrastructure, particularly accessibility and supporting facilities, along with effective promotion, is crucial for increasing tourist attraction and visits to Bira Village.